2004
DOI: 10.1007/s11661-004-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state reactions during heating mechanically milled Al/TiO2 composite powders

Abstract: Solid-state reactions between Al and TiO 2 during heating high-energy mechanically milled Al/TiO 2 composite powders have been investigated by using a combination of thermal analysis, X-ray diffraction (XRD), and various microstructural characterization techniques. When the TiO 2 particles and their interparticle spacing in the Al/TiO 2 composite powder particles are sufficiently large, the reaction between Al and TiO 2 proceeds by two steps. The low-temperature step is an interfacial reaction, which starts at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
0
28
2
Order By: Relevance
“…MECHANICAL alloying (MA), using the ball-milling or rod-milling techniques, has been widely employed for fabrication of useful advanced engineering materials, [1] including metal nitrides, [2,3,4] carbides, [5] hydrides, [6] silicates, [7] composite and nanocomposite materials, [8,9,10] and nanocrystalline materials. [11,12] The rapid solidification technique, using melt spinning or casting methods, has been used for preparing several attractive promising hard and soft magnetic metallic glassy alloys (for example, References 13 through 17), which attract increasing interest with their unique short-range atomic order.…”
Section: Introductionmentioning
confidence: 99%
“…MECHANICAL alloying (MA), using the ball-milling or rod-milling techniques, has been widely employed for fabrication of useful advanced engineering materials, [1] including metal nitrides, [2,3,4] carbides, [5] hydrides, [6] silicates, [7] composite and nanocomposite materials, [8,9,10] and nanocrystalline materials. [11,12] The rapid solidification technique, using melt spinning or casting methods, has been used for preparing several attractive promising hard and soft magnetic metallic glassy alloys (for example, References 13 through 17), which attract increasing interest with their unique short-range atomic order.…”
Section: Introductionmentioning
confidence: 99%
“…The ordered Al 3 Ti may be formed through ordering of Al(Ti) solid solution at temperatures close to the melting point of Al [9]. In the present case, gradual formation of Ti from the first step of reduction of TiO 2 and its presence together with Al causes formation of Al 3 Ti phase.…”
Section: Resultsmentioning
confidence: 61%
“…There is no detailed study on the formation mechanism of TiAl/Al 2 O 3 composite. It has been observed that the reaction takes place after the melting of Al even after extended milling [9]. It seems that the low ball-topowder mass ratio in this case did not provide sufficient energy for occurrence of the reaction in the solid state.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These intermetallics have low density, high elastic modulus, and strength at high temperatures, as well as the dimensional stability because of the passive layers resistant to oxidation and corrosion. Several potential applications have been identified for titanium aluminide alloys in aerospace, automotive, and turbine power generation industries [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%